Body image perception based on body image states scale (BISS) among dancers in Klang Valley, Malaysia / Ain Nadiah Jamaludin…[et al.] - Jamaludin, Ain Nadiah; Mohamad Dali, Basirah; Marzuki, Norfarahin (2014)
Background: Dancers are a group whose profession is dancing and believed to be predisposed with highly concerned body image and fear of appearance. Their job necessity exposed this group often to strive for thinness and concerned about their body image, hence, could lead them to engage with unhealthy behaviour such as diet and lifestyle which can cause eating disorder. Objective: This study was conducted to identify the body image perception and the level of fear of appearance and its relationship with demographic data among dancers. Method: This cross sectional study was conducted with 155 dancers in Klang Valley using Body Image State Scale (BISS), Body Shape Questionnaire (BSQ) and Fear of Negative Appearance Evaluation Scale (FNAES) through self-administered questionnaire. Height was measured by stadiometre and weight was measured by weighing scale to get their BMI status. Data was analysed using SPSS version 22.0 and statistical analysis used were frequency, mean, standard deviation and chi-square. Results: Out of 155 dancers, almost 50% of female dancers were dissatisfied with their body image. In addition, more than 50% of female dancers are having a body shape concern despite having a normal BMI status. The fear of appearance's level is also higher among female dancers compared to male dancers. Conclusion: Most of the female dancers are having higher body image dissatisfaction and fear of appearance compared to male dancers. This is true to the fact that dancer is a person whose concern to body image and fear of appearance is high.